High Expression of RECQL Protein in ER-Positive Breast Tumours Is Associated With a Better Survival - Mahmoodi, Ardalan; Shoqafi, Ahmed; Sun, Ping; Giannakeas, Vasily; Cybulski, Cezary; Nofech-Mozes, Sharon; Masson, Jean-Yves; Sharma, Sudha; Samani, Amir Abbas; Madhusudan, Srinivasan; Narod, Steven A.; Akbari, Mohammad R. (Frontiers in Oncology, 2022)
Background: RECQL (also known as RECQ1 and RECQL1) is a gene of recent interest in breast cancer and an association between high levels of RECQL protein in breast cancer tumour cells and good survival of patients has been reported. Methods: To validate this association, we measured the RECQL protein levels in tumours of 933 breast cancer patients using immunohistochemistry analysis and followed the patients for death from breast cancer. Results: Women with a level of RECQL protein above the 75th percentile had better 15-year disease-specific survival among ER-positive patients (62.5% vs. 48.7%, HR= 0.72, 95%CI= 0.52-0.98, p-value = 0.04), but not among ER- patients (48.9% vs. 48.0%, HR= 1.07, 95%CI= 0.67-1.69, p-value= 0.79). Among the ER-positive patients, high RECQL protein levels were associated with better survival among women who received tamoxifen treatment (67.0% vs. 51.5%, HR= 0.64, 95%CI= 0.41-0.99, p-value= 0.04). Conclusion: RECQL might be a new predictive marker for tamoxifen treatment among ER-positive patients.